PENGGUNAAN METODE TUTOR SEBAYA UNTUK MENINGKATKAN HASIL BELAJAR KETERAMPILAN MAKRAME KELAS VIII 1 SMP NEGERI 32 PADANG - ARMINI, Drs. Ajusril, Drs. ErwinA, M.Sn (Serupa The Journal of Art Education, 2013)
This study aim to determine the improvement of student learning outcomes for subjects woven skill in eight grade 1 SMP Negeri 32 Padang used Peer Tutor. The data in this study were collected using the research instrument and observation sheet. To see the change in students’ learning activities in the two cycles are cycles I and II. The study involved students of class VIII.1, 30 in total. Data obtained and analyzed using  percentages. The study findings suggest that the increase in learning outcomes significantly makramé skills, it can be seen from the averae pre-cycle 69.50 to 71.16 at the first cycle. At the second cycle also showed an average increase of 77.83. it can be conclude that the peer teaching method can improve learning outcomes woven skills eight grade 1 students at junior high school 32 padang. Key words : Peer Teaching Method to Improve Learning  Outcomes Macrame